Persistent Activation of Calcium‐Sensing Receptor Suppresses Bone Turnover, Increases Microcracks, and Decreases Bone Strength. (6th March 2019) - Dong, Bingzi; Endo, Itsuro; Ohnishi, Yukiyo; Mitsui, Yukari; Kurahashi, Kiyoe; Kanai, Mai; Hiasa, Masahiro; Teramachi, Jumpei; Tenshin, Hirofumi; Fukumoto, Seiji; Abe, Masahiro; Matsumoto, Toshio
Abstract: Activating mutations of calcium‐sensing receptor (CaSR) cause autosomal dominant hypocalcemia type 1 (ADH1). Patients with ADH1 exhibit similar features to patients with hypoparathyroidism, including reduced serum parathyroid hormone (PTH) and Ca with low bone turnover. Although persistent suppression of bone turnover may increase bone fragility, bone strength in ADH1 patients has been unclear. We created knock‐in mice harboring the A843E activating mutation of CaSR, mimicking severe features of ADH1 patients. The severe form of ADH1 model mice showed smaller body and bone size with lower bone mineral density (BMD) and cortical area of the femur compared with age‐matched wild‐type (WT) mice. Bone strength in the femur was lower in ADH1 mice even after correction by bone geometry and/or BMD. Microcracks were markedly increased in ADH1 mice, but were rarely detected in WT mice. There was a negative correlation between bone strength corrected by bone geometry and/or BMD and microcrack number or density in ADH1 and WT mice. Among ADH1 mice, negative correlation was still observed between bone strength and microcrack number or density. Microcracks increased with age in ADH1 mice, and were negatively correlated with bone strength. Treatment with PTH(1‐34) or a calcilytic, JTT‐305, increased bone turnover, reduced microcracks, and increased bone strength to similar levels to those in WT mice. The increase in microcracks was associated with a reduction in bone strength in ADH1 mice, and aging aggravates these changes. These results demonstrate that activating mutation of CaSR causes reduction in PTH secretion with suppressed bone turnover, that reduced bone turnover is associated with an age‐dependent increase in microcracks with a reduction in bone strength, and that both PTH(1‐34) and calcilytic ameliorate all these changes in bone turnover and strength. It is suggested that fracture susceptibility may be increased in severe types of ADH1 patients especially in the elderly. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.